Turnover rates of different collagen types measured by isotope ratio mass spectrometry - Rucklidge, Garry J.; Milne, George; McGaw, Brian A.; Milne, Eric; Robins, Simon P. (Biochimica et biophysica acta, 1992)
The rates of collagen turnover in different tissues have been estimated in growing rats previously exposed to gaseous 18O 2. The abundance of the stable isotope was measured using isotope ratio mass spectrometry following combustion of isolated collagen-derived hydroxyproline. Using this method, problems of label reutilization associated with radiolabelling methods are avoided. In general the results confirm the slow turnover rates with half-lives of total collagen in skin, muscle and gut of 74, 45 and 244 d, respectively. The use of cyanogen bromide digests of whole tissues followed by isolation of collagen type-specific peptides has allowed the comparison of turnover rates of collagen types I and III, indicating that collagen type III is turned over more rapidly than type I.